Pakistan’s Maritime Sector: A Catalyst for Economic Growth and Prosperity - Tabish, Najeeb Ul Haq; Shahzad, Prof. Dr. Sajid Mehmood; Hanif, Sidra (Journal of Nautical Eye and Strategic Studies, 2025)
The maritime sector is playing a vital role in the economic development of many countries across the globe. The trade of world is completely dependent on sea and it has also increased the importance of maritime sector in the globalized world. Maritime power is also a vital component of states’ National Power. Pakistan has been blessed with more than 1000 Km coastline. Pakistan has amazing strategic location in Arabian Sea which can play a significant role in the economic development and the protection of maritime assets of Pakistan. Maritime components can be utilized to improve the economy of Pakistan. This article is intended to highlight the potentials and prospects of Maritime Power of Pakistan for its economic development.